The Role of Police Investigators in the Process of Investigating the Criminal Act of the Laromabati Village Office (Case Study of the South Halamahera Resort Police) - Fahrid Galitan; Ridjal Junaidi Kotta; Nam Rumkel (Faculty of Law, Khairun University, 2019)
The crime of destruction of public facilities that occurred in the legal area of South Halmahera Police Station is the destruction of the Village Office of Laromabati, the crime of destruction has been regulated in Article 170 of the Criminal Code. This study uses an empirical legal approach, with research locations in South Halmahera District Police and in Laromabati Village, North Kayoa District, South Halmahera District. Sources of data obtained from primary data or data obtained directly and secondary data obtained from several books and other documents. Data collection techniques namely by interviewing directly to law enforcement officials who directly handle cases of damage to the Laromabati Village Office. The results of this study were carried out with the fact of the destruction of the Laromabati Village Office. The role of South Halmahera District Police investigators is to carry out law enforcement through investigations and investigations in order to find and collect evidence which with clear evidence of criminal acts and finding suspects. Whereas the form of handling of South Halmahera Police investigators in the case of the destruction of the Laromabati Village Office was influenced by factors of law enforcement officials and the low awareness of the community's law.